PSMA2 promotes chemo- and radioresistance of oral squamous cell carcinoma by modulating mitophagy pathway - Chun-I Wang; Cheng-Yi Chen; Ting-Wen Chen; Chun-Chia Cheng; Shu-Wen Hong; Tsung-You Tsai; Kai-Ping Chang (Cell Death Discovery)
Abstract Oral cavity squamous cell carcinoma (OSCC) represents the most prevalent malignancy among head and neck squamous cell carcinomas (HNSCCs). Standard treatment modalities include surgical resection combined with radiation and chemotherapy. However, locoregional failure remains a critical issue affecting the prognosis of OSCC patients, largely due to tumor resistance against radiation or chemotherapy. In this study, we established a gene database related to OSCC recurrence and identified PSMA2 as a novel molecule influencing prognosis in OSCC patients. An independent Taiwanese cohort confirmed that elevated PSMA2 transcript levels were associated with poorer prognosis and contributed to the chemo- and radioresistance phenotype in OSCC. Furthermore, we confirmed that PSMA2 regulates cell cycle, mitochondrial dysfunction, and mitophagy, thereby contributing to carcinogenesis and resistance. Notably, mitophagy inducer exhibit antitumor effects in PSMA2-overexpressing OSCC xenograft mouse model. Collectively, our results provide a mechanistic understanding of the atypical function of PSMA2 in promoting OSCC recurrence.